2017
DOI: 10.1016/j.cemconres.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical drying of cementitious materials

Abstract: Techniques to characterize the microstructure of hydrated cement require dried materials. However, the microstructure of hydrated products is significantly altered by high capillary forces during drying when using the conventional drying methods. To avoid drying stresses when preparing samples, we have employed supercritical drying (SCD) which has been used for decades to prepare aerogels that undergo no shrinkage during drying, but has rarely been used for cementitious materials. The pore solution is first re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…TGA measurements were performed by PerkinElmer R Pyris 1, in which specimens were heated from room temperature to 1000 • C. The measured mass change between 105 • C and 1000 • C was used to calculate the degree of hydration (DoH). The detailed procedure and equation were reported in our previous studies [72,71,69]. The NAD measurements were conducted using an ASAP 2010 apparatus, from Micromeritics (see [71] for more details).…”
Section: Mip Nad and Tgamentioning
confidence: 99%
See 1 more Smart Citation
“…TGA measurements were performed by PerkinElmer R Pyris 1, in which specimens were heated from room temperature to 1000 • C. The measured mass change between 105 • C and 1000 • C was used to calculate the degree of hydration (DoH). The detailed procedure and equation were reported in our previous studies [72,71,69]. The NAD measurements were conducted using an ASAP 2010 apparatus, from Micromeritics (see [71] for more details).…”
Section: Mip Nad and Tgamentioning
confidence: 99%
“…The detailed procedure and equation were reported in our previous studies [72,71,69]. The NAD measurements were conducted using an ASAP 2010 apparatus, from Micromeritics (see [71] for more details). The Micromeritics 9410 apparatus was used for MIP tests (see [73] for details).…”
Section: Mip Nad and Tgamentioning
confidence: 99%
“…X‐ray diffraction analysis was performed to elucidate the compositions of new and old cement specimens. Based on our facilities and time schedule, we prepared the new cement specimens using the solvent exchange method . First, small cement pieces with weights of ~10 g were separated from the major cement bulk.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes they are also compared with 2D micrographs of actual hydrated cement paste microstructure either qualitatively [2, 4] or by statistically analyzing the spatial distribution of the solid phases or capillary porosity using radial distribution functions or autocorrelation functions [810]. However, 2D micrographs are typically acquired only after interrupting hydration by solvent exchange or drying, and under the high vacuum conditions of a scanning electron microscope (SEM) These conditions may alter the microstructure considerably compared to that in a fully saturated system, especially the C−S−H [1113], although a recent report showed that solvent exchange with isopropyl alcohol followed by supercritical drying, which should exert no drying stresses on the structure, yield C−S−H morphologies observed by SEM that are at least qualitatively like those obtained by normal solvent exchange and drying [14]. In contrast, the advent of nanoscale X-ray computed tomography (nCT) has made it possible to examine the 3D microstructure of porous cementitious media with a spatial resolution on the order of tens of nanometers, and coupling tomography with nanoscale X-ray fluorescence spectrometry (nXRF) has enabled the mapping of the elemental concentrations with about the same spatial resolution [15].…”
Section: Introductionmentioning
confidence: 99%
“…These conditions may alter the microstructure considerably compared to that in a fully saturated system, especially the C-S-H, [11][12][13] although a recent report showed that solvent exchange with isopropyl alcohol followed by supercritical drying, which should exert no drying stresses on the structure, yield C-S-H morphologies observed by SEM that are at least qualitatively like those obtained by normal solvent exchange and drying. 14 In contrast, the advent of nanoscale X-ray computed tomography (nCT) has made it possible to examine the 3D microstructure of porous cementitious media with a spatial resolution on the order of tens of nanometers, and coupling tomography with nanoscale X-ray fluorescence spectrometry (nXRF) has enabled the mapping of the elemental concentrations with about the same spatial resolution. 15 Several papers published in the last few years [15][16][17][18] have shown the rich 3D data that can be acquired and analyzed with these methods, which make it possible for the first time to compare 3D microstructure against predictions of microstructure-based computer models of cement hydration.…”
mentioning
confidence: 99%